2011
DOI: 10.1103/physreva.84.023613
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study of quasi-one-dimensional Bose gas experiments via the stochastic Gross-Pitaevskii equation

Abstract: The stochastic Gross-Pitaevskii equation is shown to be an excellent model for quasi-onedimensional Bose gas experiments, accurately reproducing the in situ density profiles recently obtained in the experiments of Trebbia et al. [Phys. Rev. Lett. 97, 250403 (2006) (2010)]. To facilitate such agreement, we propose and implement a quasi-one-dimensional stochastic equation for the low-energy, axial modes, while atoms in excited transverse modes are treated as independent ideal Bose gases.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 92 publications
(162 reference statements)
6
42
0
Order By: Relevance
“…(Calculations of the position-space distribution based on a related formalism [18] were recently described in Ref. [19].) We find excellent agreement between the SPGPE results and the momentum-space measurements reported in Ref.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…(Calculations of the position-space distribution based on a related formalism [18] were recently described in Ref. [19].) We find excellent agreement between the SPGPE results and the momentum-space measurements reported in Ref.…”
supporting
confidence: 76%
“…[19]). As the SPGPE approach is suited to both equilibrium and dynamical simulations, this opens up an exciting avenue for exploring nonequilibrium phenomena in this system (e.g., quenches [30]), which cannot be explored using the YY solutions or equilibrium quantum Monte Carlo techniques.…”
Section: Fig 2 (Color Online) Examples Of the Experimental Momentummentioning
confidence: 99%
“…Such a coupled condensate-cloud description appears to be essential for accurately describing certain collective oscillations of the gas at high temperatures [65,86,87]. However, as it is based on the assumption that a well-defined condensate exists, the ZNG approach is not applicable to more general scenarios involving low-dimensional systems [34,48,88,89], regimes of turbulent matter-wave dynamics [23,45,90], or non-equilibrium passage through the transition to condensation [16,44,51].…”
Section: A Relevance To Other Theoriesmentioning
confidence: 99%
“…15 in the framework of the stochastic (projected) GrossPitaevskii equation (SPGPE) to model evaporative cooling of a pancake shaped thermal cloud and study the statistics of trapped vortices and found good agreement between experimental and numerical results. The SGPE and the SPGPE have been used before to model experimental results with success 15,35,36,[47][48][49] .…”
Section: Methodsmentioning
confidence: 99%